(1): Using find the conic that passes thru the points and .
(2): Find the circle that passes thru the points and .
Find the area of the region bounded by the conic in (1) and the circle in (2) to six decimal places.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
For the conic a x 2 + b x y + c y 2 + d x + e y = − 1 6 .
For ( 0 , 4 ) : ⟹ 4 c + e = − 4
For ( 0 , − 4 ) : ⟹ 4 c − e = − 4
For ( 2 , 0 ) : ⟹ 2 a + d = − 8
For ( − 2 , 0 ) : ⟹ 2 a − d = − 8
For ( 1 , 4 ) : ⟹ a + 4 b + 1 6 c + d + 4 e = − 1 6
⟹ c = − 1 , e = 0 , a = − 4 , d = 0 and b = 1 ⟹ − 4 x 2 + x y − y 2 = − 1 6 or 4 x 2 − x y + y 2 = 1 6 which is an ellipse since b 2 − 4 a c > 0 .
Solving for y we obtain:
y = 2 1 ( ± 6 4 − 1 5 x 2 + x )
Using the portion of the ellipse above the line y = 2 x ⟹ y 1 ( x ) = 2 1 ( 6 4 − 1 5 x 2 + x ) .
For circle ( x − a ) 2 + ( y − b ) 2 = r 2 .
For (1) ( 0 , 4 ) : ⟹ a 2 + 1 6 − 8 b + b 2 = r 2
For (2) ( 0 , 5 ) : ⟹ a 2 + 2 5 − 1 0 b + b 2 = r 2
Subtracting (1) from (2) we obtain: 9 − 2 b = 0 ⟹ b = 2 9 .
For (3) ( − 1 , 3 ) ⟹ 1 + 2 a + a 2 + 9 − 6 b + b 2 = r 2
For (1) ( 0 , 4 ) : ⟹ a 2 + 1 6 − 8 b + b 2 = r 2
Subtracting (1) from (2) we obtain: a + b = 3 and using b = 2 9 ⟹ a = − 2 3
⟹ r 2 = 2 5 ⟹ ( x + 2 3 ) 2 + ( y − 2 9 ) 2 = 2 5 .
Solving for y we obtain:
y = ± 2 5 − ( x + 2 3 ) 2 + 2 9
Using the portion of the circle below the line y = 2 9 ⟹ y 2 ( x ) = − 2 5 − ( x + 2 3 ) 2 + 2 9
You can check that ( − 1 , 3 ) satisfies the ellipse above.
From graph above the ellipse and the circle intersect at ( − 1 , 3 ) , ( 0 , 4 ) .
For ∫ − 1 0 y 1 ( x ) d x :
Let I 1 = 2 1 ∫ − 1 0 6 4 − 1 5 x 2 d x .
Let 1 5 x = 8 sin ( θ ) ⟹ d x = 1 5 8 cos ( θ ) d θ ⟹
1 5 3 2 ∫ cos 2 ( θ ) d θ = 1 5 1 6 ∫ ( 1 + cos ( 2 θ ) ) d θ = 1 5 1 6 ( θ + 2 1 sin ( 2 θ ) ) = 1 5 1 6 ( arcsin ( 8 1 5 x ) + 6 4 1 5 x 6 4 − 1 5 x 2 )
⟹ I 1 ( x ) ∣ − 1 0 = 1 5 1 6 ( arcsin ( 8 1 5 ) + 6 4 7 1 5 )
⟹ ∫ − 1 0 y 1 ( x ) d x = 1 5 1 6 arcsin ( 8 1 5 ) + 4 7 − 4 1 = 1 5 1 6 arcsin ( 8 1 5 ) + 2 3 ≈ = 3 . 5 8 7 7 3 6
For ∫ − 1 0 y 2 ( x ) d x :
Let I 2 = − ∫ − 1 0 2 5 − ( x + 2 3 ) 2 d x
Let x + 2 3 = 2 5 sin ( θ ) ⟹ d x = 2 5 cos ( θ ) d θ
− 2 5 ∫ cos 2 ( θ ) d θ = − 4 5 ∫ ( 1 + cos ( 2 θ ) ) d θ = − 4 5 ( θ + 2 1 sin ( 2 θ ) ) = − 4 5 ( arcsin ( 2 5 x + 2 3 ) + 5 2 ( x + 2 3 ) ( 2 5 − ( x + 2 3 ) 2 ) )
⟹ I 2 ( x ) ∣ − 1 0 = − 4 5 ( arcsin ( 1 0 3 ) − arcsin ( 1 0 1 ) )
⟹ ∫ − 1 0 y 2 ( x ) d x = − 4 5 ( arcsin ( 1 0 3 ) − arcsin ( 1 0 1 ) ) + 2 9 ≈ 3 . 3 4 0 8 8 1
⟹ ∫ − 1 0 y 1 ( x ) − y 2 ( x ) d x = 0 . 2 4 6 8 5 5 .